Strategic Planning for a Very Different Nursing Workforce - Weston, Marla J. (Nurse leader, 2022)
The COVID-19 pandemic amplified and intensified dramatic changes already emerging within the nursing workforce. This article examines and extrapolates from current trends to enable nurse leaders to prepare for the future nursing workforce and practice environment. Suggestions for strategic planning including imaging and prioritizing from a set of options for achieving a desired future state are offered. Strategic planning focusing on the wise use of nursing expertise and creating a positive professional practice environment can support the transition from the current crisis to a more resilient health care system supported by the full utilization of the knowledge and skills of registered nurses.